Alternative surface treatments for the repair of through-wall corrosion damage in metallic pipes with bonded plates. Issue 16 (10th December 2022) - Oliveira, M.J.; Enne, F.F.; Reis, J.M.L.; da Costa Mattos, H.S.
ABSTRACT: Through-wall corrosion damage in pipelines can be repaired using a bonded metallic patch. Several parameters influence the repair performance, such as the surface preparation. Offshore oil platforms are restricted areas, and sparkling derived from surface preparation can have drastic consequences. Additionally, an industrial climber is required to access some areas that are difficult in the repairing process. In this work, the influence of alternative, easy to apply in the field, surface preparation methods on the burst pressure in pipes with defects repaired by a bonded metallic patch is investigated. Three different methods were considered: treatment with an abrasive-free rotating bristle machine and the application of a special primer directly on the oxidized surface without any additional mechanical treatment; and wet abrasive blasting. Initially, to verify the difference between these different systems, bonded single-lap joints are analyzed and then, hydrostatic tests in 6" diameter specimens with a circular hole of 1". Although the use of a rotating bristle machine gives the best roughness and strength results, the other alternative methods are less time-consuming, assure reasonable strength, and are easier to be used in the field.